The Influence of Ewom on The Purchase Intention of Young Consumers at Online Travel Agents Through the Expansion on the Information Adoption Model (Case Study on Traveloka, Tiket.Com, Agoda, Pegipegi, Airbnb) - Siti Balqis; Refi Rifaldi Windya Giri (Journal of Economics and Business UBS, 2023)
e-WOM has become very popular in recent years due to the increasing number of contributors and the proliferation of mobile platforms for applicatios on social media. In online travel agents, it is currently known that tourist is obtain information from online review websites rather than hotel websites to decide their hotel choices, therefore eWOM significantly influences consumers purchasing decisions. This research contributes to IAM and the extended model will be tested in eWOM research on five online travel egents (Traveloka, Tiket.com, Agoda, Pegipegi, Airbnb). This study aims to examine the effect of argument quality, source credibility, information quantity, and emotional word understanding on the percived usefulness of eWOM, to analyze the effect of perceived usefulness on information adoption and to investigate the effect of information adoption on young consumers purchase intentions. The type of research used in this study is descriptive analysis with quantitative approach with CB-SEM data analysis techniques using the Amos24 program with a minimum sample of 385 respondents.The results show that argument quality, source credibility, information quantity and emotive word comprehension have positive effect on the perceived usefulness of eWOM. Perceived usefulness has positive influence on the information adoption of eWOM, which in turn predicts the young consumers’ purchase intentions. This study makes several contributions to the literature on marketing communications, in particular to eWOM research and IAM theory. Practically, this research provides knowledge and insight to online travel agent site marketers in order to increase the usability and effectiveness of eWOM to attract more young consumers.